Physical activity in Costa Rican urban population and its relationship to socio-demographic and anthropometric patterns - Gómez, Georgina (2023)
The objective of this study was to describe the amount of physical activity carried out by Costa Rican urban population and to determine its relationship to socio-demographic and anthropometric variables. A representative sample of Costa Rican urban population, made up by 798 individuals, was analyzed. The physical activity data (displacement, free time and total) were taken through the International Physical Activity Questionnaire (IPAQ). Participants were classified as active or inactive according to the internationally recommendation of physical activity. 37.1% of participants did not meet the recommendations. It was also observed that the time of physical activity was significantly longer (p< .001) in men (535.3 vs. 371.3 min/week) in younger people (584.3 min/week in the 15-19 years old group vs. 309.2 min/week in the 50-65 years old group) and in people that were not overweight (521.3 vs. 411.7 min/week). The waist circumference was significantly lower in active people (90.6 vs. 94.1 cm, p < .011), and active men also showed a lower neck circumference (38.2 vs. 39.6 cm, p < .001), lower weight (75.7 vs. 79.3 kg, p = .025) and a lower body mass index (26.1 vs. 27.9 kg/m2, p = .004). These results could be used to raise awareness on the need for improvement in the implementation of global policies and practices to promote physical activity.